Discovery of Novel Biphenyl Carboxylic Acid Derivatives as Potent URAT1 Inhibitors - Xianxin Hou; Yongcheng Wang; Yajun Yang; Zhiyan Xiao (Molecules, 2023)
Urate transporter 1 (URAT1) is a clinically validated target for the treatment of hyperuricemia and gout. Due to the absence of protein structures, the molecular design of new URAT1 inhibitors generally resorts to ligand-based approaches. Two series of biphenyl carboxylic acids were designed based on the structures of URAT1 inhibitors Epaminurad and Telmisartan via a strategy of pharmacophore fusion. Fifty-one novel compounds were synthesized and most of them showed obvious inhibition against human URAT1. A1 and B21 were identified as the most potent URAT1 inhibitors in series A and B, respectively. They exhibited IC50 values of 0.93 μM and 0.17 μM, which were comparable or superior to the clinical uricosuric drug benzbromarone. The results confirmed the effectiveness of ligand-based approaches in identifying novel and potent URAT1 inhibitors.